Pseudouridine excretion in healthy subjects and its accumulation in renal failure - Dzúrik, R; Lajdová, I; Spustová, V; Opatrný, K (Nephron, 1992)
Pseudouridine (psi) is a unique nucleoside accumulated in the sera of renal failure (RF) patients. Surprisingly data on its excretion are lacking. To get an overview, the psi serum level and urinary excretion were investigated in 73 healthy subjects (C), 16 patients not on dialysis (ND) and 12 hemodialysis patients (D). It was found: (a) psi accumulates in the sera of both ND and D patients. An inverse power correlation fits best with the relationship between serum psi and the clearance of endogenous creatinine (CCr). The amount of psi filtered in glomeruli of ND patients increases while it remains practically unchanged in D patients. However, the psi filtration load of residual nephrons increases with the decreasing CCr as a consequence of its increased serum concentration. (b) Both psi net resorption and secretion have been found in C subjects. The increased psi resorption diminishes the necessary increase of psi urinary excretion both in ND and D patients. The increase of psi resorption is marked if calculated on residual nephrons. (c) The slightly decreased psi excretion excludes the participation of its increased synthesis in its accumulation in RF. It is concluded that psi accumulation in RF is caused by the impairment of its kidney excretion and the increased psi resorption participates markedly in its retention.
Keywords: referenční hodnoty; Renal Dialysis; Kidney Failure, Chronic; ledviny; Glomerular Filtration Rate; Reference Values; pseudouridin; Kidney; Humans; chronické selhání ledvin; dialýza ledvin; lidé; hodnoty glomerulární filtrace; Pseudouridine